HAK ASASI MANUSIA DAN TANTANGAN EKSPLOITASI SUMBER DAYA ANTARIKSA - Johan Rosihan (The Juris, 2026)
Advances in space technology have brought humanity to the brink of commercializing space resources, including mining on the Moon and asteroids. These activities trigger fundamental legal debates regarding wealth distribution and the protection of human rights. This research analyzes the risks of space resource monopolies by developed nations and private corporations, which potentially infringe upon human rights—specifically the right to development and the right to the common heritage of mankind. The research problems addressed include: (1) how the international legal framework balances the commercial rights of investors with the principle of human rights protection for all humanity in space exploitation, and (2) the positions and challenges of ASEAN countries in facing the international space exploitation regulatory race. The research method employed is normative juridical with a conceptual approach through the "Common Heritage of Mankind" doctrine, a statutory approach toward the Outer Space Treaty 1967 and the Moon Agreement 1979, as well as a comparative approach within the ASEAN region, specifically between Indonesia, Thailand, and Vietnam. The results indicate a significant void in international law regarding equitable benefit-sharing mechanisms, thereby threatening the economic sovereignty of developing nations. Comparatively, ASEAN countries remain behind in codifying domestic space laws capable of protecting national interests on the global stage. This study recommends the establishment of a new international regime under the UN to guarantee inclusive distribution of space benefits and the strengthening of ASEAN space diplomacy to create collective bargaining power.